Behçet's disease: An immunogenetic perspective. Issue 6 (20th October 2018) - Salmaninejad, Arash; Zamani, Mohammad Reza; Shabgah, Arezoo Gowhari; Hosseini, Seyedmojtaba; Mollaei, Fatemeh; Hosseini, Nayyerehalsadat; Sahebkar, Amirhossein
Abstract: Behçet's disease (BD) is a chronic and rare multisystemic disorder defined by autoimmunity and inflammatory characteristics, manifested by ocular lesions, recurrent genital and oral ulcers, skin symptoms and arthritis as well as neurological, intestinal, and vascular involvement. Despite the unknown cause of BD, there is some strong documentation for immunological, genetic, environmental, and infectious factors playing a role in the pathogenesis of BD. While the nature of the genetic variants remains unidentified, many genetic risk factors are considered to contribute to BD susceptibility. Along with human leukocyte antigen gene encoding B*51 (HLA‐B*51) and areas including the major histocompatibility complex class I, genome‐wide association studies have recognized numerous other BD susceptibility genes including those encoding interleukin (IL)‐10, IL‐12 receptor β 2 (IL‐12RB2), IL‐23 receptor (IL‐23R), C‐C chemokine receptor 1 gene, signal transducer and activator of transcription 4 (STAT4), endoplasmic reticulum aminopeptidase (ERAP1), and genes encoding killer cell lectin‐like receptor family members (KLRC4‐KLRK1). It is believed that BD could be considered as a disorder lying in between autoimmune and autoinflammatory syndromes. The positive responses to classical immunosuppressive agents like azathioprine and cyclosporine and involvement of autoantigens in the initiation of the disorder are the main BD features that reflect the autoimmune nature of the disorder. In this review, we address recent findings on the role of common cytokines, antibodies and immunogenetic factors in BD.